Project management of the digital transformation of companies - S. A. Titov; N. V. Titova (Вестник университета)
The introduction of digital technologies is accompanied by serious organizational changes, leading to a radical transformation of the principles of doing business at the level of individual companies and entire industries. Most of the research on this topic draws attention to the technological aspect of this large-scale phenomenon. The problem of methods and tools  for managing the digital transformation of companies remains to a much  lesser extent studied. A huge potential for development is contained in the application of methodologies and tools for project management of transformation. This article identifies the specific characteristics of managing the digital transformation of a company and determines which project management tools are best suited for these characteristics. The study is structured as a review of scientific research using qualitative data analysis tools. The results of the study allow us to conclude that digital transformation management is characterized by the need to ensure  comprehensive alignment between technological and overall strategy. Another key characteristic is hybridity, aimed at combining flexibility and stability in management, technical and social development of the company  and innovative and regular management.